If fleas developed a rite, It would be related to the dog - Rodrigues Lima Almeida, Joao Jose [UNESP] (Pontifícia Universidade Católica do Paraná (PUC-PR), 2009)
This article highlights a set of Wittgensteinian remarks on James Frazer's texts found in The Golden Bough, put it inside the context of creation of a conceptual framework for his renewed philosophical approach after his return to Cambridge, a period comprehended between 1929-1932, and delimits the ritualistic value of his grammatical method of philosophy.
Keywords: Wittgenstein; Grammar; Ritual; Method of Philosophy